Strengthening Nationalism in Students Through Scout Activities as an Effort to Prevent Brawls Among Medan 8 State High Schools - Sihite, Daniel; Iren Bangun; Salsabila, Tengku; Jamaludin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Nationalism is an embodiment of the love of the nation that a person has in a nation and state based on Pancasila. Problems that commonly occur among students are drug abuse, bullying, smoking addiction, and the most common problem is brawls. Brawls are often carried out by students, especially among high school teenagers. This can damage the younger generation and can reduce students' sense of nationalism, because brawls have many negative impacts both on the social, emotional and educational environment. Apart from that, brawls can cause divisions. This research uses qualitative research. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. In qualitative research, researchers use interview, questionnaire and documentation methods. This research was conducted on Tuesday, October 24 2023 at SMA Negeri 8 Medan, Jl. Sampali No.23, Pandau Hulu II, sub-district. Medan Area, North Sumatra 20233. The results of this research are effective in reducing brawling activities among high school students.